2016
DOI: 10.3389/fnbeh.2016.00239
|View full text |Cite
|
Sign up to set email alerts
|

Association of Increased Serum ACE Activity with Logical Memory Ability in Type 2 Diabetic Patients with Mild Cognitive Impairment

Abstract: Background: Angiotensin-converting enzyme (ACE) is involved in the chronic complications of type 2 diabetes mellitus (T2DM) and Alzheimer's disease. This study aimed to assess the pathogenetic roles of ACE and the genetic predisposition of its insertion/deletion (I/D) polymorphism in mild cognitive impairment (MCI) among T2DM patients.Methods: A total of 210 T2DM patients were enrolled. Among these patients, 116 satisfied the MCI diagnostic criteria and 94 exhibited healthy cognition. The cognitive functions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Studies have shown that Ang II was related to AD in elder patients. Tian et al [ 111 ] analyzed different I/D single-nucleotide polymorphisms of ACE gene in T2DM patients ( n = 210). Patients with MCI presented higher ACE level and ACE activity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Ang II was related to AD in elder patients. Tian et al [ 111 ] analyzed different I/D single-nucleotide polymorphisms of ACE gene in T2DM patients ( n = 210). Patients with MCI presented higher ACE level and ACE activity.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes increased about 50% risk of Alzheimer's disease (AD) [2] with a prodromal stage called MCI, a transitional stage between normal cognition and AD dementia [3]. Previous researches suggested that uncontrolled hyperglycemia is a risk factor of T2DM with MCI [4,5]. Epide-miological evidence showed that cholesterol is also a risk factor for AD [6].…”
Section: Introductionmentioning
confidence: 99%